Tari Ngalebar - I Putu Agus Ari Yana; I Kt. Suteja; I Wayan Budiarsa (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2021)
The Mabuu - buu tradition is a cultural event, carried out every year in the context of Nyepi in the Panjer Traditional Village, Denpasar. The event has the meaning Nyomya sekala - niskala which means neutralizing, balancing Bhuana Agung and Bhuana Alit. The understanding of Nyomya is controlling oneself through good thoughts, words and deeds. In this day and age, the understanding ofNyomya is often ignored, seen from the behavior of modern society which always vents emotion. Through this phenomenon, the creators are interested in creating dance works that express unrestrained thought fluctuations, which are implemented into contemporary expressions of kerawuhan motion with the title Ngalebar. The process of creating this dance, using the method of Creating Through Dance by Y Sumandiyo Hadi, describes exploration (exploration), improvisation (experimental), and composition (formation). To ensure the creation of this work, using the theory of Imagination whichmeans the formation of motion from the results of images or imagining the meaning of Nyomya, and the theory of Aesthetics ngunda bayu which is the distribution of energy in the body. The theme of thiswork is spiritualization (formation of the soul) danced by seven dancers using the gamelanaccompaniment Gong Gede Saih Pitu in collaboration with the keyboard. Ngalebar Dance is a contemporary dance work depicting human reflection, trying to exercise self-control or introspection to achieve sekala - niskala harmony and to end it returned according to its position.Keywords: Ngalebar, Mabuu - buu, Skala - niskala and Contemporary